EFFECT OF METHANOL EXTRACT OF PANDAN LEAVES (Pandanus Amaryllifolius Roxb) AGAINST Culex Quinquefasciatus AS LARVICIDE - , WAN GUSTIKA RAZILLAH; , Dr. Budi Mulyaningsih,Apt.,M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Bancroftian filariasis is among the diseases transmitted by mosquito and Culex quinquefasciatus is the main vector in South East Asia. Filariasis elimination programme of Indonesia includes control of vector. One of the means is by larviciding. Uncontrolled use of larvicide results in larvicide resistance in Culex species. It poses the need of new alternative larvicides. Since Cx. quinquefasciatus breeds in close proximity to humans, the safety of larvicide becomes crucial. Therefore, Pandanus amaryllifolius Roxb may be potential alternative larvicide against Cx. quinquefasciatus larvae as it contains bioactive chemicals with larvicidal potency. Objective: To explore biopotency of methanol extract of P. amaryllifolius R. leaves as larvicide against Cx. quinquefasciatus larvae. To find out the relation between variance of extract concentrations and larval mortality. Design: This study is true experimental posttest only study. It started with preliminary test to obtain range of extract concentrations with 20%-80% larval mortality. Then, based on th preliminary result, range of seven extract concentrations for final test was calculated and three test repeatitions were conducted. Subjects were 4 to 5-day old Cx. quinquefasciatus larvae (Instar III or IV). Observation of larval mortality was done after 24 hours and data was analysed using probit analysis Results: LC50 and LC90 values are at 1361.308ppm and 80974.59ppm respectively. Larve response to the exposure was heterogenous with equation of regression line Y=0.7223523X + 2.736179. Conclusion: Methanol extract of Pandanus amaryllifolius Roxb leaves has larvicidal effect against instar III/IV larvae of Culex quinquefasciatus but ineffective. There is linear relationship between extract concentration and larval mortality.